A social psychological toolbox for clinical psychology - Fiedler, Klaus; Grüning, David (Zeitschrift für Psychologie, 2021)
. Translational science involves the fruitful interplay between basic research paradigms and related fields of application. One promising candidate for such synergy is the relationship between social and clinical psychology. Although the relation is principally bi-directional, such that either discipline can take the role of the basic and the applied science, we take the perspective of transfer from basic social and cognitive social psychology to applications in the clinical realm. Starting from a historical sketch of some of the earliest topics in the interface of both disciplines, we first come to conclude that truly integrative co-theorizing is conspicuously missing. Then, however, we recognize the strong potential for productive collaboration at the pragmatic level of an adaptive research toolbox containing approved methods and compact theoretical tools that carry over between disciplines. We outline the notion of a generic, provisional toolbox as distinguished from a fixed repertoire of established standard procedures. We provide examples of two subsets of tools, methods and logical principles required proper diagnostic reasoning, and theoretically founded influence tools that can enrich the repertoire of therapeutic interventions. Rather than propagating a normatively prescriptive toolbox, we interpret translational science as a pluralistic endeavor, such that different clinicians complete their personalized toolboxes in manifold ways.